Electron transfer dynamics of peptide‐derivatized RuII‐polypyridyl complexes on nanocrystalline metal oxide films1. Issue 1 (19th January 2013) - Hanson, Kenneth; Wilger, Dale J.; Jones, Sean T.; Harrison, Daniel P.; Bettis, Stephanie E.; Luo, Hanlin; Papanikolas, John M.; Waters, Marcey L.; Meyer, Thomas J.; Maran, Flavio; Toniolo, Claudio
Abstract The performance of dye‐sensitized solar and photoelectrochemical cells is strongly dependent on the electron transfer events at the electrode‐sensitizer interface. Surface‐bound peptides derivatized with chromophores have not been used in dye‐sensitized solar and photoelectrochemical cells, but they have properties for these applications that could be advantageous by exploiting secondary structure and the attachment of multiple chromophores. In this manuscript, we have investigated structure–property relationships for three metallopeptide‐based assemblies to solution and chemically bound to nanocrystalline MO2 (M = Ti, Zr) films. A particular interest was exploring the influence of increasing separation distance between a common chromophore, [Ru(bpy)2(4‐Me‐4′‐(NHCO)bpy)]2+, and the underlying oxide substrate on excited and ground state electron transfer. Rates of Ru(II) oxidation to Ru(III) at the interface were measured by cyclic voltammetry on fluorine‐doped tin oxide and cross‐surface electron transfer on TiO2. Excited state injection by [RuIII(bpy)2(bpy−)]2+ was monitored by transient absorption and time‐resolved emission. There are discernible trends in the electron transfer rate data with approximated, fully extended distances between the [Ru(bpy)2(4‐Me‐4′‐(NHCO)bpy)]2+ sites and the interface. However, the distance dependences that are observed are smaller than anticipated, a result consistent with a lack of ordered secondary structure in the surface‐bound peptide chains and a distribution of local orientations. For the surface‐bound excited states, only a small fraction undergo quenching by electron transfer to TiO2, presumably from those oriented near the surface. © 2012 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 25–37, 2013.